AHSA1 is a promising therapeutic target for cellular proliferation and proteasome inhibitor resistance in multiple myeloma - Chunyan Gu; Yajun Wang; Lulin Zhang; Li Qiao; Shanliang Sun; Miaomiao Shao; Xiaozhu Tang; Pinggang Ding; Chao Tang; Yuhao Cao; Yanyan Zhou; Mengjie Guo; et al. (Journal of Experimental & Clinical Cancer Research, 2022)
Abstract Background Currently, multiple myeloma (MM) is still an incurable plasma cell malignancy in urgent need of novel therapeutic targets and drugs. Methods Bufalin was known as a highly toxic but effective anti-cancer compound. We used Bufalin as a probe to screen its potential targets by proteome microarray, in which AHSA1 was the unique target of Bufalin. The effects of AHSA1 on cellular proliferation and drug resistance were determined by MTT, western blot, flow cytometry, immunohistochemistry staining and xenograft model in vivo. The potential mechanisms of Bufalin and KU-177 in AHSA1/HSP90 were verified by co-immunoprecipitation, mass spectrometry, site mutation and microscale thermophoresis assay. Results AHSA1 expression was increased in MM samples compared to normal controls, which was significantly associated with MM relapse and poor outcomes. Furthermore, AHSA1 promoted MM cell proliferation and proteasome inhibitor (PI) resistance in vitro and in vivo. Mechanism exploration indicated that AHSA1 acted as a co-chaperone of HSP90A to activate CDK6 and PSMD2, which were key regulators of MM proliferation and PI resistance respectively. Additionally, we identified AHSA1-K137 as the specific binding site of Bufalin on AHSA1, mutation of which decreased the interaction of AHSA1 with HSP90A and suppressed the function of AHSA1 on mediating CDK6 and PSMD2. Intriguingly, we discovered KU-177, an AHSA1 selective inhibitor, and found KU-177 targeting the same site as Bufalin. Bufalin and KU-177 treatments hampered the proliferation of flow MRD-positive cells in both primary MM and recurrent MM patient samples. Moreover, KU-177 abrogated the cellular proliferation and PI resistance induced by elevated AHSA1, and decreased the expression of CDK6 and PSMD2. Conclusions We demonstrate that AHSA1 may serve as a promising therapeutic target for cellular proliferation and proteasome inhibitor resistance in multiple myeloma.